ChemInform Abstract: Catalytic Enantioselective Synthesis of N—C Axially Chiral Phenanthridin‐6‐one Derivatives. Issue 20 (April 2016) - Hirata, Tomoaki; Takahashi, Isao; Suzuki, Yuya; Yoshida, Hiroaki; Hasegawa, Hiroshi; Kitagawa, Osamu
Abstract: Phenanthridinone derivatives bearing ortho‐substituted phenyl groups on the nitrogen atom are enantioselectively obtained by a palladium/Segphos‐catalyzed intramolecular Buchwald—Hartwig amination.